Industry Based Learning Teching Factors for Forming The Character of Vocational High School Student - Ussolikhah, Nakhma’; Fathiah, Ima; Azzahra, Fatimah (Cirebon Annual Multidiciplinary International Conference (CAMIC), 2025)
Juvenile delinquency such as truancy, brawls, and other negative behaviors are challenges that schools often face. This phenomenon is triggered by various internal factors such as lack of self-control, as well as external factors such as peer influence and lack of involvement in positive activities. To overcome this problem, SMKN 1 Cirebon applies the Teaching Factory (TeFa) learning model, an approach that combines learning in schools with industrial practices. TeFa provides students with real experience in a work environment that resembles industry, forming characters of discipline, responsibility, and cooperation. This program is effective in reducing juvenile delinquency by directing students to relevant and meaningful structured activities. Through the TeFa program, students not only gain technical skills that are in accordance with industry needs but are also trained to face the world of work through industrial culture such as fingerprint attendance, briefings, and work targets. This study uses a qualitative method with a case study approach to explore the implementation of TeFa at SMKN 1 Cirebon. Data collection techniques with observation, interviews and data analysis using Source Triangulation. The results of the study showed that TeFa succeeded in improving student discipline, reducing juvenile delinquency, and strengthening the relationship between schools and the world of work. industry can collaborate with partners such as PT. Dharma Listrik Manufaktur. TeFa as a practical solution to improve the quality of vocational education, Field Work Practices, and bridge the gap between education and the needs of the world of work.